Constitutive modeling of the stress-softening in swollen polychloroprene rubber under cyclic loading / Raihana Mohamad Fawzi - Raihana, Mohamad Fawzi (2012)
Research and development of alternative source to substitute fossil fuel are getting demanding since fossil fuels are non renewable. Thus energy insecurity becomes a critical issue. Biodiesel is one of the alternatives explored for the substitution. However, the compatibility of biodiesel with the elastomeric components such as o-rings and seals is still questionable. In practical engineering application, the materials are subjected to hostile liquid such as biodiesel which leads to swelling and is also subjected to fluctuating or cyclic mechanical loading which could lead to fatigue failure. Similarly to dry elastomer, swollen elastomer exhibit inelastic response under cyclic loading such as stress softening, hysteresis and permanent set. These inelastic responses play major role on the durability of the materials. In the present work, a simple continuum model to capture the stress softening of swollen polychloroprene is addressed. The stress softening in swollen elastomer is considered as a damage process. Thus it is described phenomenologically by a scalar quantity which depends on the swelling level and the maximum strain experienced by the materials. Moreover, the first invariant of the left Cauchy-Green Strain tensor is adopted as the scalar strain measure. The results obtained show a qualitatively good agreement between the model and experiment.